(untitled) (Marketing Journal, 2025)
The article explores the conceptual foundations of strategic management for the innovative development of construction enterprises. The necessity of forming an integrated system of strategic management aimed at ensuring sustainable growth of construction o rganizations under conditions of digital transformation and increasing competition is substantiated. The essence and structure of innovation potential are revealed, and the key factors influencing the effectiveness of strategic management are identified.